2015
DOI: 10.1021/acsnano.5b03184
|View full text |Cite
|
Sign up to set email alerts
|

Physical Principles of Nanoparticle Cellular Endocytosis

Abstract: This review article focuses on the physiochemical mechanisms underlying nanoparticle uptake into cells. When nanoparticles are in close vicinity to a cell, the interactions between the nanoparticles and the cell membrane generate forces from different origins. This leads to the membrane wrapping of the nanoparticles followed by cellular uptake. This article discusses how the kinetics, energetics, and forces are related to these interactions and dependent on the size, shape, and stiffness of nanoparticles, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
815
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(835 citation statements)
references
References 122 publications
15
815
1
4
Order By: Relevance
“…For example, for a cell membrane tension in the order of 0.05 mNÁm ¡1 and bending modulus values of 15 k B T, the length scale is approximately 50 nm [48]. Simulation [59] and experiment [60] suggest a bending modulus of k » 23 k B T (»10 ¡19 J at 300 K for DPPC gives »60 nm.…”
Section: Nanoparticle-membrane Interactions: Elastic Theorymentioning
confidence: 97%
See 2 more Smart Citations
“…For example, for a cell membrane tension in the order of 0.05 mNÁm ¡1 and bending modulus values of 15 k B T, the length scale is approximately 50 nm [48]. Simulation [59] and experiment [60] suggest a bending modulus of k » 23 k B T (»10 ¡19 J at 300 K for DPPC gives »60 nm.…”
Section: Nanoparticle-membrane Interactions: Elastic Theorymentioning
confidence: 97%
“…These mechanisms are in most cases controlled by the cell membrane via specific receptor-mediated interactions (eg clathrin, caveolin, flotollin mediated endocytosis) [42,44,45]. However, it has been demonstrated that NPs can also traverse the cell membrane via endocytosis (or exocytosis) without being involved in any specific receptor-mediated interaction [46][47][48][49]. Lipid membranes are highly flexible and the bilayer can be deformed due to NP adhesion on its surface leading to a full NP engulfment and its final uptake.…”
Section: Nanoparticle-membrane Interactions: Elastic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Filament growth and membrane deformation generate forces that promote invagination of the virus 6. Many simulation studies have focused on this process of endocytosis, and provided useful information for understanding this process 7. Cell membranes are considered as the first barrier to defend cells from external harms 8.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, self‐powered motor,11 jumper,12 oscillator,13 soft actuators,14, 15, 16 and 2D semiconductor skin17 demonstrated with this class of material shed light on their new possibilities toward more diverse applications. Here, we report a particle‐eating phenomenon of gallium‐based LMs, which mimics the biological phagocytosis process (also known as cellular‐eating, a basic cell behavior referring to the transportation of external particles into cells from across the membranes18, 19, 20, 21), and thus we call it LM‐Phagocytosis. Such phenomenon represents a wet‐processing strategy to achieve particle internalization.…”
mentioning
confidence: 98%